Autoregulation of von Willebrand factor function by a disulfide bond switch - Butera, Diego; Passam, Freda; Ju, Lining; Cook, Kristina M.; Woon, Heng; Aponte-Santamaria, Camilo; Gardiner, Elizabeth; Davis, Amanda K.; Murphy, Deirdre A.; Bronowska, Agnieszka; Luken, Brenda M.; Baldauf, Carsten; et al. (Science advances, 2018)
Force-dependent binding of platelet glycoprotein Ib (GPIb) receptors to plasma von Willebrand factor (VWF) plays a key role in hemostasis and thrombosis. Previous studies have suggested that VWF activation requires force-induced exposure of the GPIb binding site in the A1 domain that is autoinhibited by the neighboring A2 domain. However, the biochemical basis of this “mechanopresentation” remains elusive. From a combination of protein chemical, biophysical, and functional studies, we find that the autoinhibition is controlled by the redox state of an unusual disulfide bond near the carboxyl terminus of the A2 domain that links adjacent cysteine residues to form an eight-membered ring. Only when the bond is cleaved does the A2 domain bind to the A1 domain and block platelet GPIb binding. Molecular dynamics simulations indicate that cleavage of the disulfide bond modifies the structure and molecular stresses of the A2 domain in a long-range allosteric manner, which provides a structural explanation for redox control of the autoinhibition. Significantly, the A2 disulfide bond is cleaved in ~75% of VWF subunits in healthy human donor plasma but in just ~25% of plasma VWF subunits from heart failure patients who have received extracorporeal membrane oxygenation support. This suggests that the majority of plasma VWF binding sites for platelet GPIb are autoinhibited in healthy donors but are mostly available in heart failure patients. These findings demonstrate that a disulfide bond switch regulates mechanopresentation of VWF. - We demonstrate mechanochemical regulation of platelet adhesion to von Willebrand factor in thrombosis and hemostasis. - We demonstrate mechanochemical regulation of platelet adhesion to von Willebrand factor in thrombosis and hemostasis.
Gesehen am 24.03.2020